2007
DOI: 10.4049/jimmunol.179.7.4754
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 Activation Induces Normal Neutrophil Responses in a Child with IRAK-4 Deficiency: Involvement of the Direct PI3K Pathway

Abstract: Polymorphonuclear neutrophils (PMN) play a key role in innate immunity. Their activation and survival are tightly regulated by microbial products via pattern recognition receptors such as TLRs, which mediate recruitment of the IL-1R-associated kinase (IRAK) complex. We describe a new inherited IRAK-4 deficiency in a child with recurrent pyogenic bacterial infections. Analysis of the IRAK4 gene showed compound heterozygosity with two mutations: a missense mutation in the death domain of the protein (pArg12Cys) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 55 publications
3
47
0
Order By: Relevance
“…Compared with unstimulated cell controls, stimulation of human neutrophils with LTB 4 or CpG-ODN alone lead to a slight but detectable phosphorylation of both p38 kinase and JNK (Fig. 5A), as reported previously (33)(34)(35). More interesting was the fact that synergism was observed in p38 and JNK kinase activation when both LTB 4 and CpG-ODN stimulations were performed simultaneously.…”
Section: Enhanced P38 and Jnk Activation Mediated By Ltb 4 Following supporting
confidence: 86%
“…Compared with unstimulated cell controls, stimulation of human neutrophils with LTB 4 or CpG-ODN alone lead to a slight but detectable phosphorylation of both p38 kinase and JNK (Fig. 5A), as reported previously (33)(34)(35). More interesting was the fact that synergism was observed in p38 and JNK kinase activation when both LTB 4 and CpG-ODN stimulations were performed simultaneously.…”
Section: Enhanced P38 and Jnk Activation Mediated By Ltb 4 Following supporting
confidence: 86%
“…These comprise cell shape changes, CD62L shedding, priming for enhanced respiratory burst 17,[47][48][49] , chemotaxis, phagocytosis 17,50 and neutrophil extracellular trap formation induction 51 , lipid mediator production 18 , prolonged survival 49,52 and cytokine production (using, however, less pure neutrophil populations than in this study), including TNFa 53 and IL-6 (refs 48,53,54). Similarly, two studies 55,56 have reported that human neutrophils cultured in the presence of infectious respiratory syncytial virus produce IL-6 at 1 ng ml À 1 per 5 Â 10 6 cells per 3 h (498% neutrophil purity 55 ), or at 100 pg ml À 1 per 5 Â 10 5 cells per 12 h (497% purity 56 ).…”
Section: Il-6 Production By Murine Neutrophils In Vitro and In Vivomentioning
confidence: 99%
“…Pathogen recognition by TLRs promotes the activation of cellular signaling NF-jB and mitogen-associated protein kinase pathways and the subsequent activation of PMN functions for efficient bacterial clearance. The major role of the TIR-IRAK signaling pathway in immunity to infections by pyogenic bacteria is illustrated by the recent description of children with inherited IRAK-4 deficiency associated with recurrent life-threatening and invasive bacterial infections (33,34).…”
Section: Detection Of Irak4 Deficiencymentioning
confidence: 99%